The link between unemployment and suicide rate before and during economic crises - Ameir Rahmad; Wye, Chung Khain (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2022)
An economic crisis would accelerate unemployment which then could af ect people's welfare and mental health. This situation is afraid to lengthen and could trigger the suicide rates. This study aims to examining the relationship between unemployment and the suicide rate before and during the Asian Financial Crisis and the Global Financial Crisis for developed and developing countries. This study used cross-sectional data and applied the ordinaryleast squares (OLS) regression model to complete the investigation. The result indicates thatthere is a positive relationship between the unemployment rate and the suicide rate in the developing countries during the crises. Meanwhile, developed countries had dif erent relationships during dif erent crises. Furthermore, the impact of unemployment toward suicide is adversely af ecting developing countries than developed countries during a crisis. By comparing the severity between the Asian Financial Crisis and the Global Financial Crisis, the result shows that the Asian Financial Crisis is more disastrous due to excessive suicide compared to the Global Financial Crisis. This study suggests that the readiness ofthe government to face a crisis by implementing ef ective policies could lessen the impact.